2019
DOI: 10.1021/acs.analchem.9b02495
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity Using MALDI Imaging Coupled with Laser Postionization (MALDI-2) for Pharmaceutical Research

Abstract: Visualizing the distributions of drugs and their metabolites is one of the key emerging application areas of matrix-assisted laser desorption/ionization–mass spectrometry imaging (MALDI-MSI) within pharmaceutical research. The success of a given MALDI-MSI experiment is ultimately determined by the ionization efficiency of the compounds of interest, which in many cases are too low to enable detection at relevant concentrations. In this work we have taken steps to address this challenge via the first application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 50 publications
(107 reference statements)
2
90
0
Order By: Relevance
“…An innovative option to overcome this decreased ionisation efficiency is through the use of laser post-ionisation combined with MALDI-MSI (so-called MALDI-2). MALDI-2 has been demonstrated to enable an up to two order of magnitude increase in sensitivity for lipids and other molecular classes from biological tissues [25][26][27]. Recently, MALDI-2 has been combined with transmission mode MSI to enable spatial resolutions as low as 600 nm under oversampling conditions [28], but it has not yet been evaluated for oversampling using conventional front-side MALDI laser introduction.…”
Section: Introductionmentioning
confidence: 99%
“…An innovative option to overcome this decreased ionisation efficiency is through the use of laser post-ionisation combined with MALDI-MSI (so-called MALDI-2). MALDI-2 has been demonstrated to enable an up to two order of magnitude increase in sensitivity for lipids and other molecular classes from biological tissues [25][26][27]. Recently, MALDI-2 has been combined with transmission mode MSI to enable spatial resolutions as low as 600 nm under oversampling conditions [28], but it has not yet been evaluated for oversampling using conventional front-side MALDI laser introduction.…”
Section: Introductionmentioning
confidence: 99%
“…is modi cation allows a lateral resolution as low as ∼10 µm. 20) Post-ionization e ionization e ciency of MALDI is estimated to be <10 −4 relative to generated neutrals, 21,22) or even signi cantly lower depending on the compound class, which limits the sensitivity of this technique as many molecules are not detected. A method to boost the MALDI ion yield is a postionization strategy.…”
Section: Desimentioning
confidence: 99%
“…Barré et al also used MALDI-2 to enhance sensitivity and signal intensity of various pharmaceutical compounds. 22) In addition, it was shown that ibuprofen, which is not detectable with regular MALDI, was detectable as a radical cation using MALDI-2. It is hypothesized that the ionization mechanism in MALDI-2 involves resonant two-photon ionization of the matrix.…”
Section: Desimentioning
confidence: 99%
See 2 more Smart Citations